A new look at the pollution halo hypothesis: The role of environmental policy stringency - Akbulut, Hale; Burçin Yereli, Ahmet (Estudios de Economía, 2023)
The effect of Foreign Direct Investments (FDIs) on greenhouse gas (GHG) emissions, has attracted the attention of researchers in recent years. However, the indirect effects of environmental policies in the process were not sufficiently considered. This study uses a panel threshold methodology to examine the nonlinear impact of environmental policy stringency on the relationship between FDIs and GHG emissions in 25 OECD countries. Our results show a negative relationship between FDIs and GHG emissions if the countries have environmental policy stringency index above a threshold level of (2.22). The results are also supported by the fixed effects model, which indicates a threshold effect of (2.88). The threshold effect is mostly due to the stringency of nonmarket-based environmental policies.